PENGARUH PENGETAHUAN, RELIGIUSITAS, DAN KEPERCAYAAN TERHADAP MINAT MASYARAKAT MEMBAYAR ZAKAT DI BAZNAS KOTA JAMBI - Heri Suryanto, Putri Ayu Suryana; Eja Armaz Hardi; Lidya Anggraeni (Jurnal Publikasi Manajemen Informatika, 2023)
The problem that often arises in our society is to whom zakat should be given. More importantly, it is distributed directly by muzakki mustahiq, orphans, neighbors, and family. This study aims to determine the effect of knowledge, religion and belief partially and simultaneously on the public's interest in paying zakat in BAZNAS Jambi City. The type of research used is field research with a quantitative approach, where the method is accompanied by hypothesis testing. The population of this research is the people of Jambi City, while the sample of this research is 100 respondents using probability sampling technique, namely incidental sampling which is calculated by the Slovin formula. The data collection method used a questionnaire that was given directly to the respondents. Testing of the results of the questionnaire using validity and reliability tests. Analysis of research data using multiple linear regression analysis, t test, f test, R2 test, and classical assumption test. The results showed that knowledge had a partial effect on people's interests, religion had no partial effect on people's interests, trust had a partial effect on people's interests, and simultaneously or simultaneously, religiosity and belief had a significant effect on people's interest in paying zakat at BAZNAS. Jambi City.